Memorable ecotourism experiences in Taman Negara, Kuala Tahan, Malaysia - Subramaniam, Thanam (2020)
Tourism experiences at tourism destinations are essential to sustain the tourists’ destination loyalty. Studies have shown that the experiences at ecotourism destinations are different from tourism destinations because these experiences cultivate the visitors’ or tourists’ concerns towards both the nature and environment. Although previous studies were conducted in Taman Negara, most of them focused on tourists’ satisfaction, conservation and attractions with limited studies on Memorable Tourism Experiences (MTEs). Furthermore, past studies have also asserted the limitations in MTEs constructs and the literature gap between MTEs, travel motivation, place attachment, tourists’ behavioural intention and actual behaviour. Thus, the objective of this study is to introduce and examine Memorable Ecotourism Experiences (MEEs) in Taman Negara, Kuala Tahan. The study further analyses the mediating effects of MEEs between travel motivation, place attachment and behavioural intention; direct effects between behavioural intention and actual behaviour; and moderating effects of socio-demographic factors of ecotourists and travel characteristics. A total of 387 questionnaires were collected with purposive sampling technique and were used in the analysis. PLS-SEM was utilised to examine the direct and mediating effects between constructs; while Hierarchical Multiple Regression (HMR) analysis was used to evaluate the moderating effects. The results clearly indicate that travel motivation has direct effect on behavioural intention; while place attachment does not has direct effect on ecotourists’ behavioural intention. In addition, MEEs mediate the relationships between travel motivation, place attachment and ecotourists’ behavioural intention. Whereas moderating analysis revealed that the purpose of visiting (leisure, adventure and visiting family and friends) significantly moderated the ecotourists’ behavioural intention; in comparison to age, nationality, own vehicle, hotels and family and friends house which significantly moderated the ecotourists’ actual revisit and pro- environmental behaviour. Hence, it can be concluded that the mediating effects of MEEs enhance the relationships between travel motivation, place attachment and behavioural intention. In addition, this study has introduced seven new sub- constructs (freeing, adverse feelings, sociable, service, planning, education awareness and nature) of MEEs which significantly influence the ecotourists’ behavioural intention. Most of the socio-demographic variables and trip characteristics moderate the ecotourists’ actual behaviour compared to behavioural intention. Thus, the outcomes of the study provide new insights to ecotourism policy makers and stakeholders in designing forthcoming ecotourism plans, policies and regulations. The respective authorities of Taman Negara, stakeholders and service providers should create, manage and practice MEEs at ecotourism destinations in order to enhance ecotourists’ intention to revisit and pro-environmental behaviour. Taman Negara management should also focus on creating additional activities and services to generate memorable experiences and enhance the destination loyalty of visitors or tourists to the park.